2009
DOI: 10.1002/app.31632
|View full text |Cite
|
Sign up to set email alerts
|

Electrospinning of antibacterial poly(vinylidene fluoride) nanofibers containing silver nanoparticles

Abstract: Poly(vinylidene fluoride) (PVDF) nanofibrous mats containing silver nanoparticles were prepared by electrospinning. The diameter of the nanofibers ranged between 100 and 300 nm, as revealed by scanning electron microscopy. The silver nanoparticles were dispersed, but some aggregation was observed with transmission electron microscopy. The content of silver nanoparticles incorporated into the PVDF nanofibrous mats was determined by inductively coupled plasma and X-ray photoelectron spectroscopy. The antibacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 33 publications
2
29
0
1
Order By: Relevance
“…The work reported in this paper is aimed at complementing work done by three other groups [12,17,18] in addition to investigating the piezoelectric response of the PVDF/AgNPs electrospun mats. The first group [17] used 5 nm prepared AgNPs to enhance the antifouling properties of PVDF membranes and reported that the produced nanocomposite fibers became smoother and finer with addition of silver.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…The work reported in this paper is aimed at complementing work done by three other groups [12,17,18] in addition to investigating the piezoelectric response of the PVDF/AgNPs electrospun mats. The first group [17] used 5 nm prepared AgNPs to enhance the antifouling properties of PVDF membranes and reported that the produced nanocomposite fibers became smoother and finer with addition of silver.…”
Section: Introductionmentioning
confidence: 95%
“…The preparation of the PVDF/AgNPs composite fiber mats was based on previously reported methods [17,18]. PVDF/AgNPs solutions were prepared as follows: 0.0525 g of AgNPs was mixed with 20 g of the 13% PVDF solution to prepare a 2% PVDF/AgNPs stock solution.…”
Section: Preparation Of Nanofibre Matsmentioning
confidence: 99%
See 2 more Smart Citations
“…the coaxial electrospinning provides a versatile method to encapsulate immobilized antibacterial agents in the core-shell micro/nanofibers. The antibacterial mechanism of this new kind of core-shell nanofibers may be different from the mechanism of Ag-doped antibacterial nanofibers [22,23]. One reason is that the PySMPU like PUPy53 and PUPyMDI35 contains large fraction of BINA unit which have an amido group in !…”
Section: Characterizationmentioning
confidence: 93%